The Ruminations Scale — characteristics of the questionnaire and preliminar - Załuski, Maciej (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction. The meaning making focusing coping plays important role during adaptation process of patient to the serious and chronic illness. The nurse under conversation with patient can recognize patient’s thoughts, that make easier and make harder treatment and rehabilitation process. She can stimulate thoughts lead to changes in the kind of personal growth too. Aim of the study. Preliminary psychometric characteristic of research tool to recognize patient’s thoughts, as meaning-making coping. Material and methods. 89 patients during neurological, oncological and surgery treatment have been surveyed. Research tools were the following: The Ruminations Scale, The Meaning in Life Questionnaire (MLQ), The Acceptance of Illness Scale (AIS) and The Posttraumatic Growth Inventory (PTGI). Results. The results of the preliminary survey showed multiply connections between ruminations, adaptations to illness process, personal growth declarations, having the meaning in life and finding the meaning. The impact of patients age and time after illness on ruminations intensity was showed. Conclusions. The Ruminations Scale is a research tool with satisfactory reliability and internal accuracy. The factor analysis confirmed 6-factor structure of the questionnaire. The research tool need further validation surveys (external accuracy and stability).